MDM2-BCL-XL PROTACs enable degradation of BCL-XL and stabilization of p53 - Mengyang Chang; Feng Gao; Jing Chen; Giri Gnawali; Wei Wang (Compuscript Ltd, 2022)
Inhibition or degradation of the anti-apoptotic protein BCL-XL is a viable strategy for cancer treatment. Despite the recent development of PROTACs for degradation of BCL-XL, the choice of E3 ligase has been restricted to VHL and CRBN. Herein, we report the development of MDM2-BCL-XL PROTACs using MDM2 as an E3 ligase for degradation of BCL-XL. Three MDM2-BCL-XL PROTACs derived from the MDM2 inhibitor Nutlin-3, which also upregulates p53, and the BCL-2/BCL-XL inhibitor ABT-263 with different linker lengths were designed, synthesized and evaluated in vitro. BMM4 exhibited potent, selective degradation activity against BCL-XL, and stabilized the tumor suppressor p53 in U87, A549 and MV-4-11 cancer cell lines. Moreover, the combination of BMM4 and the BCL-2 inhibitor ABT-199 showed synergistic antiproliferative activity. These unique bifunctional PROTACs offer an alternative strategy for targeted protein degradation.